Does drinking water influence hospital-admitted sialolithiasis on an epidemiological level in Denmark?. Issue 4 (3rd May 2015) - Schrøder, Stine; Homøe, Preben; Wagner, Niels; Vataire, Anne-Lise; Lundager Madsen, Hans Erik; Bardow, Allan
Abstract : Objectives: Sialolithiasis, or salivary stones, is not a rare disease of the major salivary glands. However, the aetiology and incidence remain largely unknown. Since sialoliths are comprised mainly of calcium phosphate salts, we hypothesise that drinking water calcium levels and other elements in drinking water could play a role in sialolithiasis. Owing to substantial intermunicipality differences in drinking water composition, Denmark constitutes a unique environment for testing such relations. Design: An epidemiological study based on patient data extracted from the National Patient Registry and drinking water data from the Geological Survey of Denmark and Greenland retrieved as weighted data on all major drinking water constituents for each of the 3364 waterworks in Denmark. All patient cases with International Statistical Classification of Diseases 10th Revision (ICD-10) codes for sialolithiasis registered between the years 2000 and 2010 were included in the study (n=3014) and related to the drinking water composition on a municipality level (n=98). Primary and secondary outcome measures: Multiple regression analysis using iterative search and testing among all demographic and drinking water variables with sialolithiasis incidence as the outcome in search of possible relations among the variables tested. Results: The nationwide incidence of hospital-admitted sialolithiasis was 5.5 cases per 100 000 citizens per year in Denmark. Strong relations were found between the incidence of sialolithiasis and the drinking water concentration of calcium, magnesium and hydrogen carbonate, however, in separate models (p<0.001). Analyses also confirmed correlations between drinking water calcium and magnesium and their concentration in saliva whereas this was not the case for hydrogen carbonate. Conclusions: Differences in drinking water calcium and magnesium may play a role in the incidence of sialolithiasis. These findings are of interest because many countries have started large-scale desalination programmes of drinking water.